Sustainable entrepreneurship and business performance: Evidence from food and beverage outlets in East Coast Malaysia / Hajera Shah Syed - Hajera , Shah Syed (2021)
The concepts of sustainable entrepreneurship and measuring business performance using the tools of sustainability performance measurement and management have gained increasing attention over the decades. The terms such as sustainability and sustainable entrepreneurship have roots in the notion of sustainable development. On the other hand, the role of Small and Medium Enterprises (SMEs) in the economic make up of a country is a significant one. Despite, the important role of SMEs, the area of sustainable entrepreneurship practices among SMEs has been under-researched. Thus, this research aimed to study sustainable entrepreneurship practices of SME managers or manager-owners of Food and Beverage Outlets located across East Coast Malaysia (i.e. the states of Kelantan, Terengganu and Pahang). The concepts of Stakeholder theory and triple bottom line have been employed to build a robust framework for the research study. In the light of The Stakeholder theory and triple bottom line three hypotheses were developed and tested. The main objective of this study was to investigate the impact of the approach of SMEs towards people/social, profit/economic and planet/environment and positive business performance. Quantitative form of study was utilized for primary data collection. A total of 200 survey questionnaires were distributed among the SME managers or manager-owners from East Coast Malaysia. 165 valid survey questionnaires, which is a response rate of 82.5 percent, were received. The results indicated that proposed research model was a significant one as approximately 40 percent of the variance in business performance was explained by the approach towards people/social, profit/economic and planet/environment. Sustainable entrepreneurship practices towards people/social do not have a significant relationship with positive business performance. Whereas, profit/economic and planet/environment have a direct significant relationship with positive business performance. In conclusion, one of the significant theoretical contributions of this study were that the findings can be added to the existing literature of sustainable entrepreneurship practices of small and medium enterprises (SMEs). Furthermore, another primary theoretical contribution was the amalgamation of the concepts of sustainability, entrepreneurship, sustainable entrepreneurship, sustainable development and sustainable growth to build a meaningful connection among the various notions so that future researchers may derive benefit from the findings of the study. Finally, from a bigger practical perspective, the Malaysian entrepreneurs shall find meaningful information to practically design their business model resulting in the fulfilment of sustainable development goals (SDGs) as laid down by United Nations.